Petri Nets, Traces, and Local Model Checking - Cheng, Allan (BRICS Report Series, 1995)
It has been observed that the behavioural view of concurrent systems that all possible sequences of actions are relevant is too generous; not all sequences should be considered as likely behaviours. Taking progress fairness assumptions into account one obtains a more realistic behavioural view of the systems. In this paper we consider the problem of performing model checking relative to this behavioural view. We present a CTL-like logic which is interpreted over the model of concurrent systems labelled 1-safe nets. It turns out that Mazurkiewicz trace theory provides a natural setting in which the progress fairness assumptions can be formalized. We provide the first, to our knowledge, set of sound and complete tableau rules for a CTL-like logic interpreted under progress fairness assumptions. keywords: fair progress, labelled 1-safe nets, local model checking, maximal traces, partial orders, inevitability